2014
DOI: 10.1158/2159-8290.cd-13-0743
|View full text |Cite
|
Sign up to set email alerts
|

p38MAPK Plays a Crucial Role in Stromal-Mediated Tumorigenesis

Abstract: Neoplastic cells rely on the tumor microenvironment (TME) for survival and progression factors. Indeed, senescent and cancer-associated fibroblasts (CAFs) express factors that promote tumorigenesis that are collectively referred to as the senescence-associated secretory phenotype (SASP). Despite their importance in tumorigenesis, the mechanisms that control TME-derived factor expression remain poorly understood. Here we address a key unanswered question, how the SASP is sustained in senescent fibroblasts and C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
149
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 44 publications
7
149
1
Order By: Relevance
“…Consistent with this notion, Alspach and colleagues ( 8 ) show that the stroma of breast cancer is enriched in SASP proteins. These promising data underscore a gap in the study in that the functional demonstration relies exclusively on cancer cell lines.…”
Section: Viewsmentioning
confidence: 71%
See 2 more Smart Citations
“…Consistent with this notion, Alspach and colleagues ( 8 ) show that the stroma of breast cancer is enriched in SASP proteins. These promising data underscore a gap in the study in that the functional demonstration relies exclusively on cancer cell lines.…”
Section: Viewsmentioning
confidence: 71%
“…The new study by Alspach and colleagues ( 8 ) in this issue describes a posttranscriptional mechanism mediated by p38MAPK activity on AUF1 to stabilize SASP mRNA species common to both CAFs and senescent fi broblasts (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p38 MAPK function in diverse inflammatory diseases is well defined. [30][31][32] In cancer, p38 MAPK regulates DNA damage response, 33 oncogene-induced senescence, 34 senescence-associated secretory phenotype, 23,35 stromal-mediated tumorigenesis 36 and mitotic cell cycle progression. 37 We have previously shown that p38 MAPK drives microglia-derived inflammation 17 and is the convergent pathway of EGFRvIII and IL-1b signaling in glioblastoma cellderived inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe the immunoprecipitation of the RNA-binding protein AUF1 with several different factors associated with the senescence-associated secretory phenotype (SASP) (Alspach and Stewart, 2013), specifically IL6 and IL8. This protocol was originally published in Alspach et al (2014). …”
mentioning
confidence: 99%